2021
DOI: 10.1111/jvh.13527
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and geographic spreading of hepatitis B virus genotype A (HBV‐A) in Brazil and the Americas

Abstract: Hepatitis B virus genotype A (HBV-A) is disseminated in different countries around the world. It presents a high genetic diversity and is classified into seven subgenotypes (A1-A7). HBV-A1 and HBV-A2 are the most frequent and spread in almost all American countries. This study aimed to evaluate the molecular epidemiology of these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This agrees with previous studies in our country (19,25). This sub-genotype has been associated to HBV/HIV co-infection, as demonstrated in previous reports (19,37,38). Accordingly, in this study the frequency of subgenotype A2 was higher in HBV/HIV co-infected patients than in mono-infected patients.…”
Section: Acute Hepatitis B (Ahb)supporting
confidence: 93%
“…This agrees with previous studies in our country (19,25). This sub-genotype has been associated to HBV/HIV co-infection, as demonstrated in previous reports (19,37,38). Accordingly, in this study the frequency of subgenotype A2 was higher in HBV/HIV co-infected patients than in mono-infected patients.…”
Section: Acute Hepatitis B (Ahb)supporting
confidence: 93%
“…Although previous studies have reported higher rates of HBsAg and HBeAg loss in patients with genotype A (18–21), those studies did not evaluate responses by HBV subgenotype. Epidemiologic data regarding subgenotypes of A indicate that A2 is most common in Northern Europeans with CHB, whereas A1 is found largely in African, Middle Eastern, and Asian patients (22,23). In this study, HBsAg loss occurred in 4 of 6 HBeAg positive patients with genotype A2 treated with TDF alone (at weeks 71–217) and in all 3 such patients receiving combination therapy (at weeks 25–121).…”
Section: Discussionmentioning
confidence: 99%
“…By treatment arm, the percentages of participants experiencing flares in the withdrawal phase was 16 of 51 (31.4%) in the TDF arm and 11 of 60 (18.3%) in the combination arm (P 5 0.13). The percentages of participants with flares during the withdrawal phase did not differ significantly by HBeAg status at randomization (HBeAg positive: 11/36 [30.6%] vs HBeAg negative: 16/75 [21.3%], P 5 0.34).In the subset of participants who met the amended eligibility criteria and withdrew from treatment and did not have HBsAg loss before withdrawal (n 5 92),23 (25%) participants had flares after withdrawal. Most (20/23) of these participants had their first flare at or before week 208 visit.…”
mentioning
confidence: 93%
“…Wolf et al 28 demonstrated that the subgenotypes A1 and A2 were introduced in Brazil between the 16 th and 20 th centuries. The spread of HBV-A1 across the country probably occurred between 1600 and 1740, introduced directly from Africa through the slave trade.…”
Section: Discussionmentioning
confidence: 99%